A model for explaining digital addiction in adolescents: the role of self-perception, social-emotional learning, adolescent-parent relationship and peer relationships - Erez, Semih; Ağırkan, Murat (Journal of Dependence, 2024)
Objective: This study was aimed at examining the levels of digital addiction in adolescents with a regression model created with self-perception, adolescent-parent relationships, peer relationships, and social-emotional learning (SEL) skills. Method: The participants consisted of 504 high school students. The data were obtained through the Personal Information Form, the Digital Addiction Scale, the Adolescent-Parent Relationships Scale, the Friendship Quality Scale, the Self-Perception Scale, and the Social and Emotional Learning Scale. Results: Self-perception, adolescent-parent relationship, and SEL skills were significant predictors of adolescents’ digital addiction levels, while the peer relationships was not. Additionally, the regression model explains approximately 27% of the total variance of digital addiction in adolescents. Conclusion: The ability of digital platforms to compensate for negative self-perception during adolescence, coupled with inadequate SEL skills, may hinder adolescents from forming satisfying real relationships with themselves and their environment, ultimately increasing their levels of digital addiction. In families without satisfying relationships with parents where there is no positive, warm, supportive, and safe climate, this may cause digital addiction in adolescents.